Investigation of vibration parameters for needle insertion force reduction - Rehling Dennis (De Gruyter, 2020)
Many medical interventions in therapy and diagnostics require needle insertion into tissue. Common complications such as increased pain and formation of haematoma are caused by wrong needle positioning. It has been shown that pain experience and needle positioning can be improved by a reduction of insertion force, which can be achieved by vibrating the needle axially. An experimental setup has been designed to investigate the influences of different combinations of vibration frequencies (10, 100, and 200 Hz) and vibration amplitudes (20, 100, and 500 μm) during needle insertion into thin sheets of polyethylene terephthalate (PET). A customary 20 W loudspeaker was used to generate the vibration. The results indicate a maximum reduction of 73 % in puncture force and up to a 100 % reduction in shaft friction force. However, the additional vibration force generated by the vibration movement has to be high enough to generate positive effects in terms of force reduction.